Early Detection of Pancreatic Cancer—a Defined Future Using Lessons From Other Cancers: A White Paper. Issue 8 (September 2016) - Kenner, Barbara J.; Chari, Suresh T.; Maitra, Anirban; Srivastava, Sudhir; Cleeter, Deborah F.; Go, Vay Liang W.; Rothschild, Laura J.; Goldberg, Ann E.
Abstract : Abstract: The implementation of effective early detection programs has significantly improved treatment, prognosis, and life expectancy in breast, prostate, and colorectal cancers. Early-detection methods need to be developed for pancreatic ductal adenocarcinoma (PDAC), where progress during the past decades has remained slow. Addressing this need, the forum "Early Detection: Lessons Learned from Other Cancers" was held in November 2015 and presented by the Kenner Family Research Fund in partnership with the American Pancreatic Association. Leading experts from breast, prostate, and colorectal cancers described the development of early detection methods in their respective fields. Emerging opportunities for scientific advancement were subsequently identified that hold the greatest promise for the future of early detection in PDAC, including a 4-part strategic map of necessary actionable items. Knowledge from other fields must be applied to achieve large-scale change within the arena of PDAC. A major breakthrough in early detection of PDAC will occur only through a definitive interdisciplinary collaborative effort involving a critical mass of committed academic research institutions, government agencies, industry leaders, and philanthropies.